2019
DOI: 10.1136/bcr-2019-230738
|View full text |Cite
|
Sign up to set email alerts
|

Niraparib as maintenance therapy in a patient with ovarian cancer and brain metastases

Abstract: Ovarian cancer is the second the most common gynaecological malignancy in developed countries. 70% of patients relapse in the first 3 years following debulking surgery and first-line chemotherapy. Niraparib is a poly adenosine diphosphate ribose polymerase inhibitor which uses the concept of synthetic lethality in the presence of a mutation in the breast cancer susceptibility gene (BRCA), and is now recommended as maintenance treatment in patients with platinum-sensitive relapse of ovarian cancer. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“… 38 Primary peritoneal cancer IIIC >2 None BRCA1 Olaparib 22 months Gray et al, 2019. 39 Ovarian cancer IIIC >2 None BRCA1 Niraparib 17 months Favier et al, 2020. 40 Ovarian cancer IIIC Peritoneum BRCA2 Olaparib 14 months …”
Section: Discussionmentioning
confidence: 99%
“… 38 Primary peritoneal cancer IIIC >2 None BRCA1 Olaparib 22 months Gray et al, 2019. 39 Ovarian cancer IIIC >2 None BRCA1 Niraparib 17 months Favier et al, 2020. 40 Ovarian cancer IIIC Peritoneum BRCA2 Olaparib 14 months …”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have shown how specific PARPi, like niraparib, can cross the blood–brain barrier [ 71 , 72 ] and, in recent years, there have been cases reporting the use of these drugs in this subset of patients: five patients treated with PARPi had BRCA mutation; all of them achieved a progression-free survival of over 10 months [ 73 , 74 , 75 , 76 , 77 ]. Interestingly, a phase II single arm open-label study to evaluate the efficacy of niraparib in patients with BMs is ongoing [NCT04992013].…”
Section: Brcamentioning
confidence: 99%
“…-a 68-year-old woman with BM from high-grade serous OC was treated with Niraparib as maintenance therapy and remained free of disease progression for more than 17 months [120].…”
Section: Parp Inhibitorsmentioning
confidence: 99%